Effects of frequency ultrasound on the properties of zein-chitosan complex coacervation for resveratrol encapsulation. (1st May 2019) - Ren, Xiaofeng; Hou, Ting; Liang, Qiufang; Zhang, Xi; Hu, Di; Xu, Baoguo; Chen, Xinxiang; Chalamaiah, Meram; Ma, Haile
Highlights: Encapsulation can improve the stability and bioavailability of resveratrol. We successfully encapsulated resveratrol via zein-chitosan complex coacervation. Dual-frequency ultrasound treatment enhanced encapsulation and loading capacity. Crystal and secondary structure were not changed but thermal stability increased. Protein-polysaccharide coacervation with ultrasound can encapsulate polyphenolics. Abstract: In this study, resveratrol was successfully encapsulated using zein-chitosan complex coacervation. The encapsulation efficiency was markedly improved (51.4%) after chitosan coating at 1:2.5 zein/chitosan ratio, compared with 38.6% using native zein. Analysis of multi-model frequency ultrasound treatment effects on resveratrol encapsulation using zein-chitosan complex coacervation showed that 28/40 kHz dual-frequency ultrasound led to the highest encapsulation efficiency (65.2%; 31.9% increase) and loading capacity (5.9%; 31.1% increase) of resveratrol, followed by multi-frequency ultrasound at 20/28/40 kHz (17.8% encapsulation efficiency increase; 17.8% loading capacity increase). Dual-frequency ultrasound treatment significantly reduced the zein-chitosan complex coacervation particle size and reduced their distribution, however, did not change the zeta potential. Fourier transform infrared spectroscopy and fluorescence spectroscopy analysis demonstrated that ultrasound treatment had no effect on secondary structure of zein-chitosan complex but markedly decreased the fluorescence emission intensity. Differential scanning calorimetry and X-ray diffraction results indicated that Dual-frequency ultrasound treatment improved the thermal stability of zein-chitosan complex coacervation but had no effect on the crystal structure. Atomic force microscopy and scanning electron microscopy images revealed uniform distribution of zein-chitosan complex coacervation followed by ultrasonic treatment.